Dari Teologi Normatif ke Teologi Integratif-Transformatif: Rekonstruksi Epistemologis Islam sebagai Kritik dan Praksis Pembebasan Sosial - Isnaini Ajrin Karim; Salwa Ariella Belle Zandra; Faridatun Nafisah; Ali Hasan Siswanto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This article begins with the epistemological crisis in contemporary Islamic theology, which is still dominated by a normative-textual paradigm, making it less responsive to the complexity of social problems such as structural inequality, the ecological crisis, and digital disruption. The research gap lies in the absence of a theological framework that systematically integrates the dimensions of revelation, social reality, and technological development into a coherent epistemological framework. Previous studies on transformative theology tend to be partial, do not offer operational conceptual models, and have not yet made theology a tool for critical analysis of contemporary structures of injustice. This article uses an integrative theoretical approach that combines critical hermeneutics, practical philosophy, and critical sociology to reconstruct Islamic theology in a more contextual and emancipatory direction. The research method used is qualitative-conceptual with critical discourse analysis techniques and theoretical synthesis of classical and contemporary literature. The main argument of this article is that Islamic theology needs to be reconstructed from a theocentric-normative paradigm to an integrative-transformative model based on theo-anthropo-centric dialectics, which positions theology as both social critique and a practice of liberation. Within this framework, theology functions not only as normative legitimation but also as an instrument of emancipation capable of critically responding to social and digital realities. This article's scholarly contribution lies in the formulation of an Integrative-Transformative Islamic Theology model that integrates revelation, social reality, and technology as a new epistemological basis for theological studies, and expands the function of theology as a critical social theory in the context of contemporary Islam.